2022
DOI: 10.1097/md.0000000000030156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of palliative self-expandable metal stent placement in right- and left-sided malignant colon obstruction: A Honam Association for the Study of Intestinal Disease (HASID) multicenter study

Abstract: Self-expandable metal stent (SEMS) placement is commonly used for palliation of left-sided malignant colorectal obstruction (MCO). However, right-sided MCO is usually treated surgically. Recent studies that compared palliative SEMS insertion and emergency surgery in right-sided MCOs have reported conflicting results. This study aimed to compare the effectiveness of palliative SEMS placement in left-sided MCOs and right-sided MCOs and to investigate the predictive factors for clinical success and risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Malignant bowel obstruction is associated with poor prognosis also indicating disease progression [5]. The management of those patients seems extremely challenging especially due to the emergent nature of the procedure that is associated with increased morbidity and mortality compared to elective operations [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Malignant bowel obstruction is associated with poor prognosis also indicating disease progression [5]. The management of those patients seems extremely challenging especially due to the emergent nature of the procedure that is associated with increased morbidity and mortality compared to elective operations [13].…”
Section: Discussionmentioning
confidence: 99%
“…The decision to proceed with the operation is difficult and should be based on the patient's performance status and the symptoms caused by the obstruction [5,13]. Furthermore, an estimation of the patient's life expectancy is also of paramount significance [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This treatment group of preoperative decompression is more patients with early malignant intestinal obstruction. Oh et al reported that palliative self-expandable metal stent in the treatment of right malignant intestinal obstruction has a higher success rate and lower complications than the left side (17). The related stent therapy is also limited to single stenosis lesions and cannot be applied to patients with multiple abdominal metastases or extensive dissemination of tumor foci in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%